Radical theatrics : put-ons, politics, and the sixties - Peariso, Craig J. (University of Washington Press, 2014)
"From burning draft cards to staging nude protests, much left-wing political activism in 1960s America was distinguished by deliberate outrageousness. This theatrical activism, aimed at the mass media and practiced by Abbie Hoffman and the Yippies, the Black Panthers, and the Gay Activists Alliance, among others, is often dismissed as naive and out of touch, or criticized for tactics condemned as silly and off-putting to the general public. In Radical Theatrics, however, Craig Peariso argues that these over-the-top antics were far more than just the spontaneous actions of a self-indulgent radical impulse. Instead, he shows, they were well-considered aesthetic and political responses to a jaded cultural climate in which an unreflective 'tolerance' masked an unwillingness to engage with challenging ideas. Through innovative analysis that links political protest to the art of contemporaries such as Andy Warhol, Peariso reveals how the 'put-on'--the signature activist performance of the radical left--ended up becoming a valuable American political practice, one that continues to influence contemporary radicals such as Occupy Wall Street"--From publisher's website.